Nonoperative management of blunt liver and spleen injury in children. Issue 4 (October 2015) - Notrica, David M.; Eubanks, James W.; Tuggle, David W.; Maxson, Robert Todd; Letton, Robert W.; Garcia, Nilda M.; Alder, Adam C.; Lawson, Karla A.; St Peter, Shawn D.; Megison, Steve; Garcia-Filion, Pamela
<x xml:space="preserve">Abstract</x> BACKGROUND Nonoperative management of liver and spleen injury should be achievable for more than 95% of children. Large national studies continue to show that some regions fail to meet these benchmarks. Simultaneously, current guidelines recommend hospitalization for injury grade + 2 (in days). A new treatment algorithm, the ATOMAC guideline, is in clinical use at many centers but has not been prospectively validated. METHODS A literature review conducted through MEDLINE identified publications after the American Pediatric Surgery Association guidelines using the search terms blunt liver trauma pediatric, blunt spleen trauma pediatric, and blunt abdominal trauma pediatric. Decision points in the new algorithm generated clinical questions, and GRADE [Grading of Recommendations, Assessment, Development, and Evaluations] methodology was used to assess the evidence supporting the guideline. RESULTS The algorithm generated 27 clinical questions. The algorithm was supported by six 1A recommendations, two 1B recommendations, one 2B recommendation, eight 2C recommendations, and ten 2D recommendations. The 1A recommendations included management based on hemodynamic status rather than grade of injury, support for an abbreviated period of bed rest, transfusion thresholds of 7.0 g/dL, exclusion of peritonitis from a guideline, accounting for local resources and concurrent injuries in the management of children failing to stabilize, as well as the use of a guideline in patients with multiple injuries. The use of more than 40 mL/kg or 4 U of blood to define end points for the guideline, and discharging stable patients before 24 hours received 1B recommendations. CONCLUSION The original American Pediatric Surgery Association guideline for pediatric blunt solid organ injury was instrumental in improving care, but sufficient evidence now exists for an updated management guideline. LEVEL OF EVIDENCE Expert opinion, guideline, grades I to IV.